The equation above holds true for positive integers , , , and , where and is square free. Find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
let x = 2 u ⇒ d x = 2 d u
I = ∫ 0 ∞ 1 + 2 5 6 x 8 x 6 d x = 2 7 1 ∫ 0 ∞ 1 + u 8 u 6 d u
I = 2 7 1 ∫ 0 ∞ 1 + u 8 1 d u / / ∫ 0 ∞ f ( x ) d x = ∫ 0 ∞ x 2 f ( x 1 ) d x
I = 2 7 1 ⋅ 8 ⋅ sin ( 8 π ) π = 2 1 0 ⋅ sin ( 8 π ) π //see Note(1)
I = 2 1 0 ⋅ 2 1 2 − 2 π = 2 9 2 − 2 1 π \ //see Note(2)
a = 1 , b = 2 9 , c = 2 , d = 2
a × b × c × d = 2 1 1 = 2 0 4 8
Note(1) :
∫ 0 ∞ 1 + x 2 n 1 d x * we will use contour integration *
∮ 1 + z 2 n 1 d z = ∫ − R R 1 + x 2 n 1 d x + ∫ γ R 1 + z 2 n 1 d z
as R → ∞ ∫ γ R 1 + z 2 n 1 d z = 0 //seepoof(a)
∮ 1 + z 2 n 1 d z = 2 π i ⋅ ∑ z k ∈ A R e s ( f ( z k ) ) //A is the set of all poles inside contour // Residue Theorem
∮ 1 + z 2 n 1 d z = 2 π i ⋅ 2 n i ⋅ sin ( 2 n π ) 1 = 2 n sin ( 2 n π ) 2 π //see poof(b)
Now
∮ 1 + z 2 n 1 d z = ∫ − R R 1 + x 2 n 1 d x + ∫ γ R 1 + z 2 n 1 d z
a s R → ∞ 2 n sin ( 2 n π ) 2 π = ∫ − ∞ ∞ 1 + x 2 n 1 d x + 0
⇒ ∫ 0 ∞ 1 + x 2 n 1 d x = 2 n sin ( 2 n π ) π
poof(a):
∣ ∣ ∣ ∫ γ R 1 + z 2 n 1 d z ∣ ∣ ∣ ≤ M L
//where M = max ∣ ∣ 1 + z 2 n 1 ∣ ∣ and L is the length of γ R = π R which is Half circle
∣ ∣ z 2 n + 1 ∣ ∣ ≥ ∣ ∣ ∣ ∣ z ∣ 2 n − ∣ 1 ∣ ∣ ∣ ∣ = ∣ ∣ R 2 n − 1 ∣ ∣ = R 2 n − 1 // ∣ z ∣ = R and R>1
⇒ ∣ ∣ 1 + z 2 n 1 ∣ ∣ ≤ R 2 n − 1 1 ⇒ ∣ ∣ 1 + z 2 n 1 ∣ ∣ ≤ max ∣ ∣ 1 + z 2 n 1 ∣ ∣ ≤ R 2 n − 1 1
as R → ∞ ∣ ∣ ∣ ∫ γ R 1 + z 2 n 1 d z ∣ ∣ ∣ ≤ M L ≤ R 2 n − 1 π R = 0
poof(b):
let z = r e i θ ⇒ z 2 n = r
so when 1 + z 2 n = 0 ⇒ 1 + r e i 2 n θ = 0 ⇒ r e i 2 n θ = − 1
⇒ r=1 and c o s ( 2 n θ ) = − 1 ⇒ 2 n θ = ( 2 k + 1 ) π ⇒ θ = 2 n 2 k + 1 π for k=0,1,2,......,2n-1
But we will take value of k from 0 to (n-1) because the other poles are outside contour \ when k=n ⇒ θ = 2 n 2 n + 1 π > π
R e s ( f ( z k ) ) = lim z → z k ( ( z − z k ) ⋅ 1 + z 2 n 1 ) = lim z → z k ( 2 n ⋅ z 2 n − 1 1 ) = 2 n ⋅ z k 2 n z k //L'Hospital'sRule ( 0 0 )
R e s ( f ( z k ) ) = 2 n ⋅ e i ( 2 k + 1 ) π e i ( 2 n 2 k + 1 π ) = 2 n ⋅ e i 2 π k ⋅ e i π e i n π k ⋅ e i 2 n π = 2 n ⋅ ( e i 2 π ) k ⋅ e i π ( e i n π ) k ⋅ e i 2 n π / / z k = e i ( 2 n 2 k + 1 π ) // Euler's Formula
R e s ( f ( z k ) ) = 2 n − e i 2 n π ( e i n π ) k / / e i 2 π = 1 , e i π = − 1
so ∑ z k ∈ A R e s ( f ( z k ) ) = ∑ k = 0 n − 1 2 n − e i 2 n π ( e i n π ) k = 2 n − e i 2 n π ∑ k = 0 n − 1 ( e i n π ) k = 2 n − e i 2 n π ⋅ e i n π − 1 ( e i n π ) n − 1 //geometric sum
= 2 n − e i 2 n π ⋅ e i n π − 1 e i π − 1 = 2 n − e i 2 n π ⋅ e i n π − 1 − 2 ⋅ ( e − i 2 n π e − i 2 n π ) = 2 n ( e i 2 n π − e − i 2 n π ) 2 ⋅ ( i i )
= i 1 ⋅ 2 n sin ( 2 n π ) 1 / / sin ( x ) = 2 i e x − e − x
Note(2) :
sin ( 8 π ) = sin ( 2 1 ⋅ 4 π ) = 2 1 − cos ( 4 π ) = 2 1 − 2 2
= 4 2 − 2 = 2 1 ⋅ 2 − 2